Integrated evaluation of workplace exposures and biomarkers of bladder cancer among textile dyeing workers - Amal Saad-Hussein; Safia Beshir; Weam Shaheen; Inas A. Saleh; Mohamed Elhamshary; Atef M. F. Mohammed (SpringerOpen, 2024)
Abstract Background The textile industry is the second risk factor for bladder cancer, after smoking. Previous studies focused on the impact of exposure to high concentrations of bladder carcinogenic chemicals in the textile dyeing industry on the elevation of bladder cancer biomarkers. This study aimed to evaluate bladder carcinogenic air pollutants in a textile dyeing factory and investigate its role and the role of serum 25-hydroxyvitamin D (25-OH vit. D) on cancer bladder biomarkers in exposed workers. Methods A cross-sectional study was conducted. Particulate and vapor forms of polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs) were monitored in the printing, dyeing, and preparing sections of a textile factory. Bladder tumor antigen (BTA), nuclear matrix protein 22 (NMP-22), and 25-OH vit. D were estimated in all the exposed workers (147 exposed workers) and in workers not occupationally exposed to chemicals (130 unexposed workers). Results Aromatic bladder carcinogenic compounds were either in low concentrations or not detected in the air samples of working areas. BTA and NMP-22 of exposed workers were not significantly different from the unexposed. However, 25-OH vit. D was significantly lower in the exposed than unexposed workers. There was a significant inverse correlation between 25-OH vit. D and duration of exposure in exposed workers. Conclusion The mean levels of PAHs and VOCs were within the safe standard levels in the working areas. The non-significant difference in BTA and NMP-22 between the exposed and unexposed groups suggests the presence of occupational exposures to safe levels of bladder carcinogenic aromatics, while the significantly lower 25-OH vit. D levels among the exposed than the unexposed groups could suggest the potential association of 25-OH vit. D with occupational exposures to low levels of PAHs and VOCs, and this association was found to be inversely correlated with the duration of exposures. Accordingly, more specific predictor tests must be applied for early diagnosis of bladder cancer among the exposed workers.